Stability Assessment Through Dynamic Light Scattering and Rheological Study of Hexanoic Acid-Surface-Modified Cerium Oxide Nanoparticles in Cyclohexane at Low Concentration - Hossain, Muhammad Zamir (Jagannath University Journal of Science, 2024)
The stability of 1wt% cerium oxide (CeO2) nanoparticles in cyclohexane is assessed in this paper. To do so, first, n-hexanoic acid (C6-) surface-modified CeO2 nanoparticles were synthesized by heating the aqueous Ce(OH)4 suspension at 400 °C and characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), high regulation transmission electron microscopy (HRTEM), Fourier transform infrared (FTIR) spectroscopy and thermogravimetric analysis (TGA). XRD pattern indicated the crystalline structure and TEM showed the cubic shape of the synthesized CeO2 nanoparticles with an average size of 4.5 nm. Next, 1 wt% CeO2–cyclohexane dispersion (nanofluids) was prepared simply by dispersing the required amounts of CeO2 nanoparticles in cyclohexane. Finally, the stability of CeO2–cyclohexane was assessed by dynamic light scattering (DLS) and rheological study. DLS measurement revealed that the 1wt% CeO2–cyclohexane nanofluid has good dispersibility with a small DLS diameter ( 6 nm) comparable to that of the pristine particle diameter measured by TEM. Also, the rheology study depicted the Newtonian behavior of prepared nanofluids which indicated its excellent stability. Jagannath University Journal of Science, Volume 11, Number 1, June 2024, pp. 23−30